Design and testing of a horizontal rock bed for high temperature thermal energy storage. (1st October 2019) - Soprani, Stefano; Marongiu, Fabrizio; Christensen, Ludvig; Alm, Ole; Petersen, Kenni Dinesen; Ulrich, Thomas; Engelbrecht, Kurt
Highlights: A rock bed for high-temperature energy storage with horizontal air flow was tested. Buoyancy forces influenced temperature distribution, lowering efficiency. Different rock bed and flow configurations were tested to optimize performance. Charge and round trip efficiencies were used as figures of merit. Optimized configuration increased charge efficiency by 17%. Abstract: Integration of energy storage infrastructures into electrical grids represents a crucial milestone in the transition towards energy systems with high penetration of renewables. However, the high cost of the currently available technologies is a significant barrier for their implementation on the industrial scale. High temperature thermal energy storage systems, in combination with bottom steam cycles, are being investigated as potential cost-effective alternatives to traditional large-scale energy storage technologies. In this study, the performance of a rock bed high temperature energy storage unit is experimentally investigated. The rock bed has a storage capacity of 450 kWhth, was built to store heat at 600 °C and is characterized in terms of thermal efficiencies. Charge and discharge cycles were performed for different operating conditions and the temperature distribution across the bed was analyzed. A particular focus was set on the study of the impact of buoyancy forces on the temperature gradient inside the bed and on the storage unit efficiency. Different charging powers, flow concepts and rock bed configurations were discussed to optimize storage operations and led to an improvement in efficiency of the charging phase of 17%. A thermal round trip efficiency of around 68% was estimated for the best configurations and different improvement approaches were discussed for future research.